Kontribusi Kualitas Pelayanan dan Persepsi Harga terhadap Loyalitas Pelanggan di Perusahaan Logistik Nasional - Helfi, Fendy; Ricardianto, Prasadja; Maemunah, Siti; Abidin, Zaenal; Farisyi, Sofwan (Institut Transportasi dan Logistik Trisakti, 2024)
The main problems of the research are the frequently late deliveries that make customers’ inconvenience and the employees often postpone to make Goods Import Notifications and to respond to emails which make customers’ disappointment and finally choose other companies. The research objective is to determine the contribution of service quality, price perception and their implications for loyalty through customer’s satisfaction in Mahkota Logistik Indoraya. The research used Quantitative method with Path analysis techniques of SmartPLS3.3. The total research sample was 100 importers. The result shows that there is a positive and significant direct and indirect effect of the service quality and perceived price on the customer’s satisfaction. The key finding is that there is still a lack of communication between employees and customers related to imported goods delivery. Price perception, such as competitive tariff for imported goods services, good communication, good experience, thoroughness in work, and smooth and fast delivery of goods, should be fulfilled to increase customers’ loyalty to the Company.